Avaliação comparativa da espermatogênese de homens azoospérmicos em diferentes etiologias - Fabíola de Araújo Resende Carvalho (2017)
The current knowledge on the causes of azoospermia is mainly focused on clinical assessments, with no indication of which germ and/or somatic components of the testicular parenchyma are compromised. In the present study, we compared the spermatogenic process of men affected by four different common etiologies that lead to azoospermia: congenital bilateral agenesis of vas deferens (AD); orchiepididymitis (OE); varicocele (VA) and mumps orchitis (MO), through the use of morphofunctional approaches in a controlled sample collection. The testicular parenchyma from AD and OE patients did not show major spermatogenic alterations, while in VA and MO patients the impairment was severe, showing a large amount of fibrotic and Sertoli cell only tubules. The spermatogonial population was significantly reduced in VA and MO patients, even though their proliferative capacity was retained. Furthermore, plasma FSH and LH levels increased in VA and MO patients, suggesting Sertoli and Leydig cells impairments. Despite these damages, the preservation of spermatogonial proliferation in patients with VA and MO raises the possibility of these patients becoming biological parents through assisted reproduction.